Phenotypes and ATP7B gene variants in 316 children with Wilson disease - Lu, Z K (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2022)
Objectives: To summarize the clinical phenotypes and the variation spectrum of ATP7B gene in Chinese children with Wilson's disease (WD) and to investigate their significance for early diagnosis. Methods: Retrospective analysis was performed on the clinical data of 316 children diagnosed as WD in Guangzhou Women and Children's Medical Center during the period from January 2010 to June 2021. The general situations, clinical manifestations, lab test results, imaging examinations, and ATP7B gene variant characteristics were collected. The patients were divided into asymptomatic WD group and symptomatic WD group based on the presence or absence of clinical symptoms at the time that WD diagnosis was made. The χ2 test, t test or Mann-Whitney U test were used to compare the differences between groups. Results: Among the 316 children with WD, 199 were males and 117 were females, with the age of 5.4 (4.0, 7.6) years at diagnosis; 261 cases (82.6%) were asymptomatic with the age of 4.9 (3.9, 6.4) years; whereas 55 cases (17.4%) were symptomatic with the age of 9.6 (7.3, 12.0) years. The main symptoms invloved liver, kidney, nervous system, or skin damage. Of all the patients, 95.9% (303/316) had abnormal liver function at diagnosis; 98.1% (310/316) had the serum ceruloplasmin lever lower than 200 mg/L; 97.7% (302/309) had 24-hour urine copper content exceeding 40 μg; only 7.4% (23/310) had positive corneal K-F rings, 8.2% (23/281) had abnormal MRI signals in the lenticular nucleus, and all of them had symptoms of damage in liver, kidney or nervous system. Compared with the group of symptomatic WD, asymptomatic group had higher levels of serum alanine aminotransferase and lower levels ceruloplasmin and 24-hour urine copper [(208±137) vs. (72±78) U/L, (55±47) vs. (69±48) mg/L, 103 (72, 153) vs. 492 (230, 1 432) μg; t=9.98, -1.98, Z=-4.89, all P<0.001]. Among the 314 patients completing genetic sequencing, a total of 107 mutations in ATP7B gene were detected, of which 10 are novel variants, and 3 cases (1.0%) had large heterozygous deletion (exons 10 to exon 11) in ATP7B gene. The percentage of missense mutation in asymptomatic WD children was significantly higher than that in symptomatic WD (81.5% (422/518) vs. 69.1% (76/110), χ²=8.47, P<0.05). WD patients carrying homozygous variant of c.2 333G>T had significantly low levels of ceruloplasmin than those not carrying this variant ((23±5) vs. (61±48) mg/L, t=-2.34, P<0.001). Conclusions: The elevation of serum ALT is an important clue for early diagnosis of WD in children, while serum ceruloplasmin and 24-hour urine copper content are specific markers for early diagnosis of WD. In order to confirm the diagnosis of WD, it is necessary to combine the Sanger sequencing with multiplex ligation-dependent probe amplification or other testing technologies